Sol-gel Derived Warfarin – Silica Composites for Controlled Drug Release - S. Dolinina, Ekaterina; V. Parfenyuk, Elena (Current Drug Delivery, 2017)
Background: Warfarin, commonly used anticoagulant in clinic, has serious shortcomings due to its unsatisfactory pharmacodynamics. One of the efficient ways for the improvement of pharmacological and consumer properties of drugs is the development of optimal drug delivery systems. Objective: The aim of this work is to synthesize novel warfarin – silica composites and to study in vitro the drug release kinetics to obtain the composites with controlled release. Methods: The composites of warfarin with unmodified (UMS) and mercaptopropyl modified silica (MPMS) were synthesized by sol-gel method. The composite formation was confirmed by FTIR spectra. The concentrations of warfarin released to media with pH 1.6, 6.8 and 7.4 were measured using UV spectroscopy. The drug release profiles from the solid composites were described by a series of kinetic models which includes zero order kinetics, first order kinetics, the modified Korsmeyer-Peppas model and Hixson-Crowell model. Results: The synthesized sol-gel composites have different kinetic behavior in the studied media. In contrast to the warfarin composite with unmodified silica, the drug release from the composite with mercaptopropyl modified silica follows zero order kinetics for 24 h irrespective to the release medium pH due to mixed mechanism (duffusion + degradation and/or disintegration of silica matrix). Conclusion: The obtained results showed that warfarin – silica sol-gel composites have a potential application for the development of novel oral formulation of the drug with controlled delivery.
Keywords: release mechanism